A clinically relevant method to screen for hepatic steatosis in overweight adolescents: a cross sectional study. Issue 1 (December 2015) - Saad, Vera; Wicklow, Brandy; Wittmeier, Kristy; Hay, Jacqueline; MacIntosh, Andrea; Venugopal, Niranjan; Ryner, Lawrence; Berard, Lori; McGavock, Jonathan
Abstract Background To develop a screening algorithm to detect hepatic steatosis in overweight and obese adolescents. Methods We performed a cross sectional study of 129 overweight adolescents 13–18 yrs. The primary outcome, hepatic steatosis was defined as an intracellular triglyceride content > 5.5 mg/g and quantified using1 H-magenetic resonance spectroscopy. Primary predictor variables included, alanine and aspartate transaminases (ALT/AST) and features of the metabolic syndrome. Results Hepatic steatosis was present in 33 % of overweight and obese adolescents. Adolescents with hepatic steatosis were more likely to be boys (adjusted OR: 4.8; 95 % CI: 2.5–10.5), display a higher waist circumference (111 ± 12 vs 100 ± 13 cm, p  < 0.001) and have metabolic syndrome (adjusted OR: 5.1; 95 % CI: 1.6–16.4). Serum ALT predicted hepatic steatosis in boys (AUC: 0.82; 95 % CI: 0.70–0.95;p  < 0.001) but not girls (AUC = 0.63; 95 % CI: 0.46–0.75, p  = 0.16). An ALT >20 U/L, combined with the presence of metabolic syndrome, male gender and an elevated waist circumference provided the best model (AUC 0.85) with high sensitivity (72 %) and specificity (82 %) and positive and negative predictive values of 61 % and 89 % respectively. Conclusions Serum transaminases provide modest predictive value for hepatic steatosis in youth. The ALT threshold for predicting hepatic steatosis is significantly lower than current clinical thresholds for predicting non-alcoholic fatty liver disease. The addition of ALT, presence of the metabolic syndrome and male gender significant improve the ability to predict hepatic steatosis.